Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2018
DOI: 10.3389/fpls.2018.01583
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of Selenium Accumulation, Localization and Speciation in Buckwheat–Implications for Biofortification

Abstract: Buckwheat is an important crop species in areas of selenium (Se) deficiency. To obtain better insight into their Se metabolic properties, common buckwheat (Fagopyrum esculentum) and tartary buckwheat (F. tataricum) were supplied with different concentrations of Se, supplied as selenate, selenite, or Astragalus bisulcatus plant extract (methyl-selenocysteine). Se was supplied at different developmental stages, with different durations, and in the presence or absence of potentially competing ions, sulfate, and p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
13
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 22 publications
(14 citation statements)
references
References 47 publications
1
13
0
Order By: Relevance
“…The greatest absorption of this element might have taken place because it is chemically similar to sulfur. Thus, the roots easily absorb and metabolize them through high affinity sulfate transporters in the plasmatic membrane (Chomchan et al, 2017) and incorporate routes with plant proteins to form selenocysteine (SeCys) and seleno-methyonine (Se-Met) (White, 2016); then, they move without chemical modification through the xylem up to the leaves before reducing to other compounds (Jiang et al, 2018;Alves et al, 2020). Similar results were reported (Andrade et al, 2018) when increased Se content was found in fruit as a result of adding it in the nutritional solution.…”
Section: Seleniumsupporting
confidence: 58%
“…The greatest absorption of this element might have taken place because it is chemically similar to sulfur. Thus, the roots easily absorb and metabolize them through high affinity sulfate transporters in the plasmatic membrane (Chomchan et al, 2017) and incorporate routes with plant proteins to form selenocysteine (SeCys) and seleno-methyonine (Se-Met) (White, 2016); then, they move without chemical modification through the xylem up to the leaves before reducing to other compounds (Jiang et al, 2018;Alves et al, 2020). Similar results were reported (Andrade et al, 2018) when increased Se content was found in fruit as a result of adding it in the nutritional solution.…”
Section: Seleniumsupporting
confidence: 58%
“…In addition to increasing the total Se content, some attention has also been given to the effects of biofortification approaches on Se species and their bioaccessibilities (Gong et al., 2018). All three Se species, selenate, selenite, and Astragalus bisulcatus plant extract (MeSeCys), accumulated 15 to 40 mg Se kg −1 DW in the seeds of both common and tartary buckwheats, and the Se localized in the seed embryo was in the forms of SeMet, MeSeCys, and γ‐Glu‐MeSeCys (Jiang, El Mehdawi, et al., 2018). It is proposed that selenate is the most effective Se form for biofortification in soil, as selenite is rapidly adsorbed on clay colloids, rendering it poorly available to plants in many soils, and selenate is usually also more effective than selenite in foliar application (Lyons, 2018; Wang et al., 2020).…”
Section: Selenium In Cereals: Content and Biofortificationmentioning
confidence: 99%
“…(Jiang, El Mehdawi, et al. (2018) obtained the Se K‐edge μXANES spectra of buckwheat seeds and performed least‐squares linear combination fitting (LCF) of the spectra at a range of 12,630 to 12,850 eV using a standard library including 52 Se compounds, and the resultant data indicated that organic Se species predominated (96% to 100%) in the buckwheat seeds, with the C‐Se‐C configuration attributed to SeMet, MeSeCys, and γ‐Glu‐MeSeCys. The XANES and HPLC‐ICP‐MS techniques had a good agreement in the analysis of SeMet in Se speciation for bulked rice grains.…”
Section: Analysis Of Selenium: From Total Amount To Speciationmentioning
confidence: 99%
“…Buckwheat is a potential selenium‐biofortified crop with rich nutrition and good health functions 8 . China is one of the main buckwheat‐producing countries.…”
Section: Introductionmentioning
confidence: 99%